Liver fibrosis regression and progression during controlled hepatitis B virus infection among HIV–HBV patients treated with tenofovir disoproxil fumarate in France: a prospective cohort study. Issue 1 (1st January 2017) - Boyd, Anders; Bottero, Julie; Miailhes, Patrick; Lascoux‐Combe, Caroline; Rougier, Hayette; Girard, Pierre‐Marie; Serfaty, Lawrence; Lacombe, Karine
Abstract: Introduction : Long‐term tenofovir disoproxil fumarate (TDF) use has been associated with significant regression of liver fibrosis during hepatitis B virus (HBV) mono‐infection, yet little is known during HIV–HBV coinfection. The aim of this study was to evaluate the evolution of liver fibrosis and its determinants in TDF‐treated coinfected patients. Methods : In this prospective cohort study, 167 HIV–HBV‐infected patients initiating TDF‐containing antiretroviral therapy were included. Fibrosis was assessed using the FibroTest® at baseline and every six to twelve months. Risk factors for fibrosis progression (F0–F1–F2 to F3–F4) and regression (F3–F4 to F0–F1–F2) were evaluated. Results : At baseline, 134 (80.2%) patients had detectable HBV‐DNA (median = 4.93 log10 IU/mL, IQR = 2.94–7.15) and 104 (62.3%) had hepatitis B "e" antigen‐positive serology. Median follow‐up was sixty months (IQR = 36–93). In the 47 (28.1%) patients with F3–F4 baseline fibrosis, 7/47 (14.9%) regressed to F0–F1–F2 at last follow‐up visit. Fibrosis regression was significantly associated with higher CD4+ cell counts ( P = 0.009) and lower fasting triglyceride levels ( P = 0.007) at TDF‐initiation. In the 120 (71.9%) patients with F0–F1–F2‐baseline fibrosis, 20/120 (16.7%) progressed to F3–F4 at last follow‐up visit. Fibrosis progression was associated with male gender ( P = 0.01), older age ( P = 0.001), from low/moderate HBV‐endemic country ( P = 0.007), lower nadir CD4+ cell count ( P = 0.03), higher fasting glycaemia ( P = 0.03) and anaemia ( P = 0.004) at TDF‐initiation. Control of HBV replication at end of follow‐up was extensive (88.1%), while no HBV‐related factors emerged as predictors of progression/regression. Incidence of severe liver‐related events was low ( n = 4, rate = 0.5/100 person‐years). Conclusions : Liver fibrosis levels are stable for most coinfected patients undergoing TDF, despite control of HBV replication. Nevertheless, a concerning amount of liver fibrosis progression did occur, which could be partly explained by metabolic abnormalities and past severe immunosuppression and requires further evaluation.